Alterations in miRNA expression patterns in whole blood of OSCC patients - Ries, Jutta; Vairaktaris, Eleftherios; Kintopp, Rita; Baran, Christoph; Neukam, Friedrich Wilhelm; Nkenke, Emeka (In Vivo, 2014)
Aberrant microRNA (miRNA) expression in blood of cancer patients is a common finding. The present study aimed at evaluating the differences in miRNA expression in whole blood samples of oral squamous cell carcinoma (OSCC) patients compared to healthy controls.Microarray based miRNA profiling was performed on whole blood samples of 20 OSCC patients and 20 healthy volunteers and the differences in expression patterns between the two groups were evaluated. The results were validated by Reverse Transcription quantitative-Polymerase Chain Reaction (RT-qPCR) in 50 OSCC patients and 35 volunteers.21 miRNAs were identified to be significantly differentially expressed in whole blood of OSCC patients compared to healthy controls. The impact of miR-186 (p=0.002), miR-494 (p=0.001) and miR-3651 (p=0.0001) could be validated by RT-qPCR.The aberrant expressions of miR-186, miR-494 and miR-3651 in whole blood of OSCC patients may serve as the basis for establishing minimally-invasive screening methods for OSCC based on miRNAs as biomarkers.
EVALuna2:24185